Initial development of IEEE Very Small Size Soccer robots: Electromechanics, Computer Vision System and Navigation Strategy - Ryan Henrique Xavier Ferreira; Pedro Lucas da Silva; Vinícius Caputo Resende de Oliveira; Carlos Dias da Silva Junior; Elias José de Rezende Freitas (The Journal of Engineering and Exact Sciences)
This paper presents the initial development of the IEEE Very Small Size Soccer (VSSS) robots, including the modeling and 3D printing of mechanical components, the integration of embedded electronics, a computer vision system, and the simulation of a navigation strategy. The proposed computer vision system can capture and process images during the VSSS match to provide the robots' and the ball's positions and velocities. From these odometry data, the proposed navigation strategy based on vector fields calculates commands to the robots, allowing different robot roles in the soccer match (striker, defender, and goalkeeper). This strategy, implemented in a simulator, is intuitive and has a low computational cost.